The Solid Phase Extraction of Some Metal Ions Using Palladium Nanoparticles Attached to Silica Gel Chemically Bonded by Silica-Bonded N-Propylmorpholine as New Sorbent prior to Their Determination by Flame Atomic Absorption Spectroscopy - M. Ghaedi; M. Rezakhani; S. Khodadoust; K. Niknam; M. Soylak (The Scientific World Journal)
In this research at first palladium nanoparticle attached to a new chemically bonded silica gel has been synthesized and has been characterized with different techniques such as X-ray diffraction (XRD), fourier transform infrared (FT-IR), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Then, this new sorbent (chemically modified silica gel with N-propylmorpholine (PNP-SBNPM)) was efficiently used for preconcentration of some metal ions in various food samples. The influence of effective variables including mass of sorbent, flow rate, pH of sample solutions and condition of eluent such as volume, type and concentration on the recoveries of understudy metal ions were investigated. Following the optimization of variables, the interfering effects of some foreign ions on the preconcentration and determination of the investigated metal ions described. At optimum values of variables, all investigated metal ions were efficiently recovered with efficiency more than 95%, relative standard deviation (RSD) between 2.4 and 2.8, and detection limit in the range of 1.4–2.7 ng mL−1. The present method is simple and rapidly applicable for the determination of the understudied metal ions (ng mL−1) in different natural food samples.